White Paper on Joint Replacement Status of Hip and Knee Arthroplasty Care in Germany (Springer Berlin Heidelberg, 2018)
White Paper on Joint Replacement This White Paper details the status of hip and knee arthroplasty care in Germany. Hip and knee replacements are amongst the most frequently performed procedures and usually become necessarily due to age-related wear of the joint, osteoarthritis and fractures of the femoral neck. In light of demographic change, demands with regard to standards of care and the procedures are likely to rise. Contents • This White Paper contains information on indications, procedures, health economic aspects and the healthcare system stakeholders involved. • It portrays current developments with regard to the prevalence of hip and knee arthroplasty, the healthcare situation and quality of care within the chain of medical care. • This book is complemented by a chapter assessing the current situation from an expert perspective with contributions from renowned experts in the fields of science, medical technology and medical practice. This book addresses people involved in shaping and representing the healthcare system from a variety of fields including medical professions, health insurances and health sciences as well as journalists and patient representatives.